(untitled) (Research, Society and Development, 2021)
The ease of access to information through the various social networks, has become potentially harmful, considering that the population’s habit of recommending drugs to a relative, friend or acquaintance through the use of consultation on social networks has led to an increase the irrational use of medicines. In this way, the objective of the research was to assess how much hyperinformation increased the irrational use of medicines and self-medication during the COVID-19 pandemic, in addition to the consequences of the spread of fake news regarding the treatment of the virus without the guidance of a qualified professional. An exploratory and descriptive methodology was used with the application of an online questionnaire for students in the pharmacy course and employees of a private college in the interior of Bahia, with 54 participants. However, the results were significant, regarding the influence of these platforms on the consumption of medicines, mainly for the preventive treatment of COVID-19, about 73.6% of the individuals carried out self-medication for fear of being contaminated, although 81.9% of these participants do not fit into the risk group. In addition, most respondents reported being more anxious and stressed about the information conveyed. Despite the various means available to obtain information, it is necessary to carry out a greater inspection in relation to the veracity of the news and circulating reports. In addition to the appreciation of the health professional, especially the pharmacist responsible for the last link between the patient and the continued care that helps in reducing self-medication.